(untitled) (Research, Society and Development, 2020)
The purpose of this case report / case series was to analyze the pattern of alveolar bone repair after extraction with the use of a collagen membrane associated or not with lyophilized bovine bone (Bio-Oss). The sample consisted of six adult patients, aged from 40 to 60 years, with indication of extraction of the upper incisors and subsequent rehabilitation with dental implants, three participants were randomly distributed in the following groups: Test - Bio-Oss associated with collagen membrane absorbable; Control - blood clot associated with an absorbable collagen membrane. Alveoli with significant bone loss, probe greater than 4 mm, uncontrolled systemic changes and smoker were excluded. The less traumatic extractions, followed by anti-inflammatory and antibiotic protocol. Computed tomography images from the preoperative time (T0) and after 4 months (T1) were used to measure bone filling. The data were compared using the T test, considering a 5% significance level. Less resorption was observed in the test group (p = 0.002). The technique of preserving the alveolar ridge with Bio-Oss and absorbable membrane was satisfactory to prevent changes in the contour of the tissue.